Obinutuzumab for treatment of membranous nephropathy in patients positive and negative for the phospholipase A2 receptor antibody: case reports - Wang, Jinmeng; Wu, Wenfeng; Wu, Huiyi (Frontiers in Immunology, 2025)
IntroductionMembranous nephropathy (MN) is a common cause of nephrotic syndrome (NS) in adults. Without treatment, two-thirds of patients with MN develop nonprogressive chronic kidney disease or end-stage renal disease within 10 years. Obinutuzumab (OBZ), which binds to CD20 and leads to a pronounced depletion of B cells, may elicit a better therapeutic response in patients with refractory MN who do not respond to rituximab or who have recurrent episodes.MethodsWe describe two MN patients, one positive and one negative for the M-type phospholipase A2 receptor antibody (PLA2R Ab). Both patients had poor responses to rituximab, but had different responses to OBZ. ResultsThe patient positive for PLA2R Ab had an immunologic response, and the patient negative for PLA2R Ab had a nearcomplete clinical response.DiscussionOBZ appears to be a suitable alternative when other treatment options are ineffective or contraindicated. The efficacy of OBZ for treatment of refractory MN needs to be verified by large-scale multicenter clinical trials.